2020
DOI: 10.1080/15389588.2020.1817416
|View full text |Cite
|
Sign up to set email alerts
|

Health status and quality of life among road users with permanent medical impairment several years after the crash

Abstract: Objective: Improvements in road infrastructure and vehicle safety have been achieved in many countries during the last decades. As the number of fatalities have dropped, the consequences of non-fatal injuries have been brought into focus. Therefore, the objective was to investigate selfreported health status and health-related quality of life several years after the crash for road-users that sustained injuries resulting in permanent medical impairment (PMI). Methods: A self-administered questionnaire using ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…More bicyclists had injuries to the upper extremities, while head injuries and injuries to the ‘vertebral column and spinal cord’, and ‘torso’ were more common among the car occupants. This is also in line with previous findings [ [5] , [6] , [7] , [8] , 15 ]. Other road users (including mostly motorcyclists) had a lower proportion of injuries to the head, face, and neck in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…More bicyclists had injuries to the upper extremities, while head injuries and injuries to the ‘vertebral column and spinal cord’, and ‘torso’ were more common among the car occupants. This is also in line with previous findings [ [5] , [6] , [7] , [8] , 15 ]. Other road users (including mostly motorcyclists) had a lower proportion of injuries to the head, face, and neck in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…For male patients, injury frequencies were ranked the same as female patients (Figure 1), with the most frequent being pelvis (bony; 35.6%) followed by spleen (16.8%), liver (12.5%), small intestine (12.0%), kidney (8.0%), large intestine (5.94%), pancreas (5.71%), pelvis (organ; 3.1%), and stomach (<1%). There were no significant sex differences in proportions of injury by region [χ 2 (64) = 72.0, p = 0.23].…”
Section: Injury Patternsmentioning
confidence: 99%
“…Atwood et al (1) demonstrated greater relative fatality risk (on average, 2.9% higher fatality risk for female front row occupants vs. male) for females in vehicles with the newest generation of safety equipment, but the differences between male and female occupants' fatality risk fluctuate across age groups. Stigson et al (2) report a greater risk of permanent medical impairment (PMI) in females compared to males, and countermeasures designed to mitigate this risk (specific to "neck" region injury, which is the region most associated with PMI) were not equally effective in men and women (3). Nutbeam et al (4) found that female patients were more frequently entrapped after crash, and that entrapped male and female patients had differing injury patterns.…”
Section: Introductionmentioning
confidence: 99%
“…This measure has been developed to estimate the risk for a patient of suffering a medical impairment at a specific level 1-3 years after the accident, based on the body part and the severity from the AIS classification of injuries using the method described by Malm et al (2008). The RPMI metric has been validated in relation to sick leave and perceived quality of life (Elrud et al, 2019;Stigson et al, 2020). The Swedish Transport Administration defines a serious injury in the road traffic environment as an injury that leads to a PMI of above 1% (PMI1+) and a very serious injury as an injury that leads to a PMI of above 10% (PMI10+) (Trafikverket, 2020).…”
Section: Measurementsmentioning
confidence: 99%